Fight apartheid...Killer of children - Anti-Apartheid Poster Calender July 1978 - Cummings, Pat, (1977)
In 1976/7 the American Committee on Africa (ACOA) held an anti-apartheid poster contest and produced calenders for the years 1978 and 1979 from these posters in cooperation with the UN Centre Against Apartheid.